USE OF PORTRAITS IN TRADEMARKS (STUDY ON THE CASE OF THE USE OF MRS MENEER'S PORTRAIT) - Fitrianda, Widiya; Sunarmi, Sunarmi; Saidin, Saidin (Inspiring Law Journal, 2024)
The use of portraits in trademarks creates polemics because copyright and trademarks are part of the IPR regime which have different protection concepts and objectives. This research aims to determine, examine and analyze the legal arrangements regarding the transfer of rights to the trademark "Jamu Cap Portrait Nyonya Meneer"; to find out, study and analyze the legal protection for the use of the portrait of Nyonya Meneer in the trademark “Jamu Cap Portrait Nyonya Meneer”; and to find out, study and analyze the judge's considerations in decision no. 2/Pdt.Sus-HKI/Cipta/2020/PN Niaga Smg regarding the portrait used in the trademark. The method used in this research is a normative legal research method with the approach used being a statutory approach and a case approach. The research results show that trademark rights can be transferred based on the provisions of Article 41 paragraph (1) letter f of Law no. 20 of 2016 and the transfer is permanent. Provisions regarding the use of portraits in trademarks are not clearly regulated in the 2014 UUHC and Law no. 20 of 2016. However, it can be implicitly found in Article 9 paragraph (1) and Article 12 paragraph (1) of the 2014 UUHC and in Article 21 paragraph (2) letter a of Law no. 20 of 2016. Protection of the economic rights of the portrait of Nyonya Meneer has ended, while the protection of moral rights is still valid because they are eternally attached to their creator. Protection for the portrait of Madame Meneer was given to the photographer. The Panel of Judges decided that the Plaintiff's claim was error in persona, but what was meant was the photographer who was the creator or copyright holder of the portrait which was never mentioned in this case